Analysis of STB Optimization for Enhancing Multimedia Services on OLT Network in the Telecommunication Engineering Laboratory Building - Nuril, Sania; Atmadja, Martono Dwi; Waluyo , Waluyo; Darmono, Hendro; Soelistianto, Farida Arinie (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The internet network is currently developing very rapidly, both in the fields of education, health, coffee shops, e-commerce, and so on. An example of using an internet network is WLAN. WLAN is wireless communication that uses radio waves as a data transmission medium. The form of implementation of this WLAN is Wi-Fi (Wireless fidelity). Wi- Fi generally works on the 2.4 GHz frequency. Microstrip antenna is a type of antenna that can be used for wireless communications. Microstrip antennas have the advantages of being small, cheap and light. This research discusses the design and manufacture of microstrip antennas which aim to widen bandwidth in Wi-Fi applications in the form of hexagonal patches arranged in a 4x4 array. The result of this research is an external device, namely a microstrip antenna, which can increase data transfer capacity and works on the Wi-Fi frequency, namely 2.4 GHz. This research is in accordance with the antenna test parameters, which have a return loss value of -14.52 dB and a VSWR of 1.5. The bandwidth produced by the 4x4 hexagonal patch microstrip antenna is 162 MHz. The results of the power level implementation of the 4x4 hexagonal array microstrip patch antenna were -37 dBm, able to increase the signal reception level by 12 dBm from the built- in antenna which was -49 dBm. These results show a better increase in power level than the built-in antenna with a difference of 12 dBm.